Enigma Politisasi Teks antara Otoritarian dan Egalitarian - Prihantoro, Hijrian A. (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
This article lies on the basic assumption of the heavy influence of power relation in interpreting religious texts. That is because the meaning of religious texts is often determined by the framework of interpretation and the model used by the exegetes. The discursive relations between the exegete and his tendency of political interest in the dialectical discourse of texts (al-na?? ) and power (al-sul?ah), are likely potential to produce a rhythm of meaning that is non-humanitarian (al-lâ insânîyah). As a result, religious texts that should be interpreted in egalitarian sense are of marginalized. This study attempts to trace the basic paradigm of the interpretation of the khilâfah as an aqidah to the power as political ideology until the emergence of the movement of takfîrî. These three terms are a series of interpretive concepts in the framework of naz}arîyat al-tafwîd} al-ilâhî which are translated into the theory of divine authority. At this point, the enigma of politicizing religious texts comes into two models of interpretation: authoritarian and egalitarian.